Multi-screening: practices and motivations - Dias, Patrícia (2015)
The proliferation of mobile devices with internet access, along with increasing rates of adoption of smartphones and tablets, are resulting in the emergence of new use practices, among which simultaneous activities in different screened-devices. This paper explores the motivations that drive multi-screening behavior and the benefits or gratifications perceived by multi-screeners. Our theoretical framework articulates a discussion of the concept of multi-screening itself, along with a description of the most common practices, with an overview of previous research in the Mobile Communication subfield on the motivations for mobile phone adoption and use. In addition, cognitive changes related to intense and frequent use of digital technologies are also addressed. Our empirical work consists of focus group discussions with multi-screeners, exploring the goals, needs, preferences and expectations associated to these practices, focusing more particularly on the most common multi-screening binomial – using the smartphone or tablet while watching television. Our results identify two main types of motivations for multi-screening: utilitarian (associated with making a better use of time and being more effective in accomplishing tasks) and affective (related to a constant and pressing need of being up-to-date with what is going on in the world and being connected to one’s network of close relationships). Concerning attention distribution, our research identifies the smartphone as the preponderant medium, as it ‘drives’ the focus of attention, while the television tends to operate in the ‘background’.